The effect of auditing fees on the relationship between auditor time pressure and profit quality - Zahra Mashyekh Pul; Reza Fallah (Big Data and Computing Visions)
The purpose of this study is to investigate the effect of audit fees on the relationship between auditor time pressure and profit quality. The statistical sample of this research includes the financial information of 125 companies in the period 2016-2019. This research is a descriptive-correlation type and regression method and fixed effects method have been used to estimate the model. The results show that the auditor time pressure has a negative and significant relationship with the quality of companies' profits and the audit fee has a positive and significant effect on the relationship between auditor time pressure and profit quality.